PREVENTION EFFORT OF DENGUE THROUGH EDUCATION AND PRACTICE OF THE 3M PLUS MOSQUITO NEST ERADICATION MOVEMENT FOR ELEMENTARY STUDENT IN WAGIR DISTRICT, MALANG REGENCY - Shafa Maulida; Amandus Michael Martin; Maulana Wildan Saputra; Astika Wirabhatari; Alidha Nur Rakhmani; Siti Haryanti (Universitas Brawijaya, 2024)
Dengue is a virus that can infect humans and be transmitted through mosquito bites, causing dengue hemorrhagic fever (DHF) and problems of the public health sector. To date, there have been several national strategies to achieve targets in combating DHF, systematically continued and carried out by the East Java Provincial Health Office up to the level of the Public Health Center, including health promotion activities, surveillance, control of risk factors, case detection, and graded case management, with a focus on prevention of Mosquito Nest Eradication (PSN) using 3M Plus (Drain, Bury, Cover). Since January 2024, there are 26 new cases of DHF found in the Wagir subdistrict, Malang Regency. Various factors can influence this increase, one of the causes being the lack of awareness among the people of Wagir about preventive measures such as 3M Plus. Methodologically, this study utilized a pre-experimental one-group pretest-posttest design. The research consisted of two phases: pre-intervention and intervention. In the pre-intervention phase, the primary data collected through a questionnaire on respondent characteristics, as well as a questionnaire on Knowledge, Attitude, and Practice regarding Dengue among 35 fourth and fifth-grade students at SDN Jedong 2, selected through purposive sampling. The relationship between respondent characteristics and knowledge, attitudes, and practices regarding dengue examined using regression analysis. The intervention phase involved dengue education through educational media such as posters, leaflets, and teaching aids. Additionally, pre and post-tests were conducted. Subsequently, the data from these tests were analyzed using the Wilcoxon test. The Wilcoxon test indicates that the intervention significantly increased knowledge scores after the intervention (p < 0.05) with a result of p = 0.000. There is a significant relationship between knowledge, attitude, and dengue-related behaviors. In conclusion, there was an increase in respondents' knowledge, attitudes, and behaviors regarding dengue after the intervention. Active involvement from students, teachers, parents, and community health workers is needed to improve the attitudes and behaviors of the local community to reduce the incidence rate.